The higher education “revolution” in Sudan and its impact on research in higher education institutions. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2010)
This paper aims to present the effects of higher education “revolution in Sudan in the early 1990s on its research situation. In this context higher education encompasses all post-secondary education including both public and private universities, institutes, colleges, diploma and research centres in the country (NCHESR, 2009). The higher education “revolution” has expanded student enrolments, opened door for female students, made higher education accessible (open university) and reduced the socio-economic cost by having regional universities. Nevertheless, the “revolution” reform has led to the degrading culture of research and concentration on teaching only.